Impact of preoperative HbA1c on postoperative complications after elective major abdominal surgery: a systematic review protocol - Hairil Rizal Abdullah; Hui Hua Li; Joanna Kae Ling Wong; Yuhe Ke; Yi Jing Ong (BMJ Open)
Introduction Diabetes has an increasing worldwide prevalence. It is known to be a predisposing factor for postoperative complications. Preoperative glycaemic control strategies should be pursued as glycaemic control could serve as a modifiable risk factor. Glycated haemoglobin (HbA1c), a marker of 3-month average glycaemic control, has been shown in meta-analyses to predict postoperative complications in cardiothoracic, bariatric and orthopaedic surgery. However, there is no meta-analysis in the major abdominal surgery population, in whom morbidity may be higher due to the nature of the surgery. Understanding the association between HbA1c and postoperative complications could help in preoperative risk prognostication, counselling and glycaemic target selection. The aim of this systematic review and meta-analysis is to evaluate all evidence on the association between preoperative HbA1c and postoperative complications in elective major abdominal surgery, and to investigate the threshold HbA1c level before postoperative complication rates increase.Methods and analysis This review will be performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols guidelines. PubMed, Embase, Cochrane Central Register of Controlled Trials, Google Scholar and China National Knowledge Infrastructure will be searched for all original studies. Study selection, data extraction, risk of bias and quality assessment will be conducted by two independent reviewers. The primary outcome is the association between preoperative HbA1c and major postoperative complications (Clavien Dindo 3–5), and the secondary outcome is the association between HbA1c and overall postoperative complications. Data management and synthesis will be performed using Microsoft Excel and Stata to derive pool estimates.Ethics and dissemination No ethics approval is required as only secondary data will be used. Findings will be disseminated through peer-reviewed journals and conference presentations.PROSPERO registration number CRD42020167347.